Manipulation of the surface density of states of Ag(111) by means of resonators: Experiment and theory - Fernández, Joaquín (2016)
We show that the density of surface Shockley states of Ag(111) probed by the differential conductance G(V)=dI/dV by a scanning-tunneling microscope (STM) can be enhanced significantly at certain energies and positions introducing simple arrays of Co or Ag atoms on the surface, in contrast to other noble-metal surfaces. Specifically we have studied resonators consisting of two parallel walls of five atoms deposited on the clean Ag(111) surface. A simple model in which the effect of the adatoms is taken into account by an attractive local potential and a small hybridization between surface and bulk at the position of the adatoms explains the main features of the observed G(V) and allows us to extract the proportion of surface and bulk states sensed by the STM tip. These results might be relevant to engineer the surface spectral density of states, to study the effects of surface states on the Kondo effect, and to separate bulk and surface contributions in STM studies of topological surface states.